THE PORTRAIT OF RUXANDA IN THE OPERA ”ALEXANDRU LĂPUŞNEANU” OF THE BESSARABIAN COMPOSER GHEORGHE MUSTEA - Luminiţa GUŢANU (Studia Universitatis Babeş-Bolyai. Musica)
This study aims at describing the methods and means of expression used by the composer Gheorghe Mustea in portraying the character Ruxanda. The dialectics of the heroine’s character is presented in a wide range of moods, which I will analyse by synthesizing the two emotional areas: the X-major-clear sphere / the Y-minor-obscure sphere.